A new record of Vaccinium carneolum (Ericaceae) in Indonesian New Guinea - Wendy Achmmad Mustaqim (Jurnal Biologi Papua, 2019)
Vaccinium carneolum (Ericaceae), previously known only from Papua New Guinea, has been recently collected from Arfak Mountains, Papua Barat Province. It represents the first record of this species in Indonesian New Guinea. A description and illustration, as well as a brief discussion, are provided.Key words: Ericaceae, New Guinea, Plant taxonomy.